Pengaruh Efikasi Diri, Dukungan Sosial dan Adaptabilitas Karir terhadap Kecemasan Karir Mahasiswa Tingkat Akhir Fakultas Ekonomi dan Bisnis - Ghita, Jehan Nailla; Dara, Despinur; Wolor, Christian Wiradendi (CV. ULIL ALBAB CORP, 2026)
Career anxiety is one of the psychological issues commonly experienced by final-year students, particularly when facing an uncertain labor market and transitioning from higher education to the workforce. This study aims to analyze the effects of self-efficacy, social support and career adaptability on career anxiety among final-year students of the Faculty of Economics and Business, Universitas Negeri Jakarta. A quantitative survey approach was used with 155 respondents from Management and Digital Business programs (class of 2022) selected through probability sampling. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS 4. Results indicate that self-efficacy and social support each have a negative and significant effect on career anxiety, while career adaptability shows a negative but non-significant effect. The R-square value indicates that the three variables explain 87.2% of career anxiety variance. This study recommends that universities strengthen self-efficacy development, optimize social support, and provide integrated and applicable career development services.